Removal of Iron(III) from Model Solution Using Jordanian Natural Zeolite - AL-ANBER, M. (Asian Journal of Chemistry, 2010)
The possibility of using Jordanian natural zeolite (JNZ) as non-treated have been investigated for removing of Fe3+ from a model solution of (1000 ppm) at a correlation of liquid to solid phases, v:g = 50:1. It has been found out that the specific surface of zeolite takes leading part at the adsorption of Fe3+ from the aqua solution with different concentrations. The thermodynamics of adsorption has been described with the most appropriate isotherms uptake of Fe3+ using zeolite. The adsorption of Fe3+ equilibrium isotherm, which is constructed at 20, 30, 40, 50ºC is studied at a constant percentage of 1 % HNO3 model solution and the ratio of sorbate to sorbent are identified. The methods of working are studied, along with their physical and chemical properties of the material towards magnetic properties of sorbate and electrical conductivity of the remaining sorbent solution.